Early Signs of the Cardiovascular System in Athletes with Symptoms of Connective Tissue Dysplasia - Thuc, Dao Chanh (Journal of Sports Research, 2018)
The purpose of the study was to improve the medical and pedagogical support of the training process of athletes with signs of connective tissue dysplasia by substantiating the early criteria of acute physical overstrain of the cardiovascular system. 132 athletes were examined, 31 of them with signs of systemic involvement of connective tissue in the dysplastic process. Early signs of overstrain of cardiac function during exercise of athletes with signs of connective tissue dysplasia were symptoms of disturbance of myocardial relaxation by the indicators of diastolic function of the heart, therewith the ejection fraction at rest can be maintained at normal levels. The presence of signs of connective tissue dysplasia in athletes with different predicted states requires sports doctors and trainers to conduct in-depth analysis and differential diagnostics of clinical forms in order to prevent complications during training competitive loads.